Clinical Acceptability of Crown Margins Versus Marginal Gaps as Determined by Pre-Doctoral Students and Prosthodontists - Michael R. Bronson, BS, DDS;1 Terry J. Lindquist, DDS, MS;2 (Journal of Prosthodontics, 2005)
Marginal integrity is a very important element in evaluating a restoration; however, there is no agreement in definition of a clinically acceptable margin